Philippine medical thesaurus on anatomy in waray - Azura, Leo Christian A., Jr (2013)
The field of medicine is arguably one of the most significant branches of science and technology. There has been increasing funding both from the government and private sector for the past few years. In fact, there are more drugs and health care products available, distributed and used now by the public than it was ten years ago. The quality of life and longevity of humans have dramatically improved in the past few decades; much of it can be attributed to the advancement and improvement of medical techniques.